Pengaruh Iklim Organisasi Sekolah Terhadap Motivasi Berprestasi untuk Mewujudkan Kinerja Pembelajaran - Ahmad Naib Komarudin (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2022)
From this value, it is obtained that the decision Ho is rejected and H1 is accepted, so thatthe School Organizational Climate (X) variable has an effect on Motivation (Y) Achievement and Learning Performance (Z). The significance of the value of the test results above is also supported by the magnitude of the value of determination (R2YZX) of 0.1246 which also shows the magnitude of the contribution of School Organizational Climate to Achievement Motivation to realize Learning Performance, which is 12.46%, while the re-maining is 0.8754 or 87 ,54% influenced by other variables not included in the model. Theresults of testing the sub-hypothesis: School Organizational Climatehas a significant effecton Achievement Motivation, School Organizational Climate has no significant effect onlearning performance, and Achievement Motivation has a significant effect on learning performance. This study found a number of important problem findings: First, on variableX (School Organizational Climate), the findings of the problems that are considered important are the level of teacher participation in school organizations is still low despite theavailability of adequate facilities and infrastructure and located in the boarding school environment. Second, on the Y variable (achievement motivation), the findings of the problem that are considered important are the teacher's motivation in the learning process is stillnot strong. Third, on variable Z (learning performance), the findings of important problems include: Teacher performance in learning is not optimal, also in teaching and learning activities (KBM) the majority of teachers do not complete teacher administration. Theoretically, the research results have implications for the theories that form the basis of the research variables, which basically can function if the school's organizational climate and learning motivation can actually be implemented based on existing theories, but in reality these theories are notcan be fully implemented.